Access to 1, 2‐Dihydroisoquinolines through Gold‐Catalyzed Formal [4+2] Cycloaddition. Issue 26 (23rd May 2014) - Xin, Zhuo; Kramer, Søren; Overgaard, Jacob; Skrydstrup, Troels
Abstract A new synthetic route to the privileged 1, 2‐dihydroisoquinolines is reported. This method, which relies on a gold‐catalyzed formal [4+2] cycloaddition between ynamides and imines, provides a new retrosynthetic disconnection of the 1, 2‐dihydroisoquinoline core by installing the 1, 8a CC and 2, 3 CN bonds in one step. Both aldimines and ketimines can be used as substrates. In addition, one example of dihydrofuropyridine synthesis is also demonstrated.